A Note on a Point in Value and Capital - Morishima, M. (Review of Economic Studies, 1953)
A Note on a Point in Value and Capital Get access M. Morishima M. Morishima Osaka Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 21, Issue 3, 1953, Pages 214–217, https://doi.org/10.2307/2295774 Published: 01 January 1953